TRADISI LARANGAN PERNIKAHAN KAKAK ADIK KANDUNG DITAHUN YANG SAMA PERSPEKTIF SOSIOLOGI HUKUM ISLAM DI KECAMATAN MUARA SABAK TIMUR KABUPATEN TANJUNG JABUNG TIMUR - Umi Khoirun Nisa; Illy Yanti; M. Nazori Majid (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
This study was prepared with the aim of examining the tradition of prohibiting marriage between siblings in one year in the perspective of the sociology of Islamic law. This phenomenon is often found in communities that have certain traditions or customs, where marriages between siblings that occur in the near future or within the same year are considered taboo or prohibited. If this tradition is violated, Javanese people believe that there will be disasters or bad things that are not wanted to happen to the family. The main reasons this tradition is still cultivated are following the ancestors from generation to generation, because of the belief that if violated will get a disaster, because it follows the Javanese calendar, and because the Javanese community accepts. This research uses a qualitative research method with an Islamic legal sociology approach. Which in this research process uses data collection methods, through library research and field research, interviews, observation, and writing which are systematically arranged, studied, and a conclusion is drawn in relation to the problem under study. Thus from this research it can be concluded that the review of the sociology of Islamic law, the phenomenon of the tradition of prohibiting the marriage of siblings in the same year in the sub-district of Muara Sabak Timur is included in the category of 'urf. In terms of its validity, the prohibition of marriage of siblings in the same year in East Muara Sabak District is included in the category of Al-'urf alfasid because normatively it contradicts the text and the basic rules that exist in Shara' and does not meet the requirements of 'urf sahih which can be determined as a legal reference. In the perspective of the sociology of Islamic law, although not explicitly mentioned in legal texts, the principle of maintaining kinship relations and avoiding things that can damage the family structure is the rationale that underlies the prohibition of this tradition.